Perception of the Educational Environment in Physiotherapy: Reflections on the DREEM Tool - Batista Garcet, Yoiler; Villavicencio Cedeño, Lissette Beatriz (Spanish Journal of Medical Education, 2025)
This letter to the editor comments on the recently published article on the evaluation of the educational environment using the DREEM instrument among Physiotherapy students at Taif University. The relevance of the study is highlighted, and the validity of the DREEM as a diagnostic tool across diverse cultural contexts is reinforced. Through a critical analysis of the results, the letter emphasizes the presence of perception gaps based on gender and academic level, an issue previously documented in the literature. Institutional actions are proposed to enhance student well-being and promote a more inclusive, participatory, and equitable educational experience. The letter aims to encourage the use of DREEM as a tool for the continuous improvement of educational quality in health sciences.